Tingkat Pemahaman Guru PJOK Terhadap Penanganan Cedera di Sekolah Dasar Negeri Se-Kecamatan Ngasem - Wirapratama, Bima Ilham; Kurniawan, Wing Prasetya; Sugito, Sugito (YLPK Mahardhika, 2024)
This research is motivated by the results of the observation of researchers, in PJOK learning in one of the public elementary schools in the Ngasem sub-district, there are PJOK teachers who are wrong in handling injuries. The problem in this study is how the level of understanding of PJOK teachers on injury handling in public elementary schools in the Ngasem sub-district. This study uses quantitative descriptive research techniques, the sampling used is using saturated sampling techniques, with all populations used as samples, and the number of samples is 17 with data collection techniques using questionnaire techniques. This study concludes that the level of understanding of public elementary school PJOK teachers in the Ngasem sub-district is in the very good category with the average result of the data obtained is 28.70. Based on the conclusion, suggestions can be recommended, namely: (1) teachers in learning can carry out safe learning for students. Also provide insight to students about handling injuries in accordance with one of the teacher's duties, namely the teacher as a facilitator. (2) Schools should provide adequate and safe facilities and infrastructure for students. (3) For other researchers who are interested in examining the level of understanding of PJOK teachers about handling injuries, they should conduct research on handling injuries associated with other elements and a larger number of samples.